SENEMBAH IN THE VORTEX OF HISTORY: CONTINUITY AND CHANGES IN LOCAL POWER IN EAST SUMATRA (1862-1946) - Nur Aini; Pujiati Pujiati; Nuhung Nuhung (SOSIOEDUKASI, 2025)
This study explores the historical dynamics of Kejeruan Senembah as a local power entity in East Sumatra during the period 1862–1946. The main focus is to trace the continuity and transformation of political authority in the context of colonial governance and social change in the region. Kejeruan Senembah originated as a traditional institution established with the endorsement of the Aceh Sultanate and later evolved into a crucial component within the political structure of the Deli Sultanate. This research employs the historical method, encompassing four stages: heuristics, source criticism, interpretation, and historiography. The primary sources include colonial archives, local literature, interviews with key informants, and visual documents such as maps and photographs from KITLV and Delpher collections. The findings reveal that Kejeruan Senembah played a strategic role in maintaining local stability through a customary Karo-based social structure and served as an intermediary between colonial authorities, the sultanate, and indigenous communities. However, Dutch intervention and the shifting political landscape leading up to and following Indonesian independence triggered changes in the power structure, culminating in territorial fragmentation and the transformation of political legitimacy after 1946. This study concludes that the case of Kejeruan Senembah is vital in reconstructing regional historical narratives that have often been marginalized in national historiography.